Antinociceptive effect of extracts of Marrubium astracanicum Jacq. aerial parts - Niloofar Kahkeshani; Milad Gharedaghi; Abbas Hadjiakhoondi; Mohammad Sharifzadeh; Mahnaz Khanavi (Mashhad University of Medical Sciences, 2017)
Objective: The genus Marrubium is used for treatment of joint pain, gout, stomach-ache and colic in Iranian Traditional Medicine. Marrubium astracanicum Jacq. (M. astracanicum) is a native species in the flora of Iran. The aim of this study was to evaluate the antinociceptive properties of various extracts of aerial parts of M. astracanicum.Materials and Methods: Antinociceptive activities of total hydroalcoholic extract (THE) and its n-hexane (non-polar) and residual partition (polar) fractions were analyzed using formalin test in mice. Morphine (5 mg/kg) and normal saline were used as positive and negative controls, respectively.Results: Intraperitoneal administration of THE (50, 100 and 200 mg/kg), non-polar fraction (200 mg/kg) and polar fraction (100 and 200 mg/kg), 30 min before formalin injection, caused significant analgesic activity in acute phase (0-5 min after formalin injection) of formalin test (p0.05 in comparison with morphine).  In chronic phase (15-60 min after formalin injection), non-polar and polar fractions (50, 100 and 200 mg/kg) showed significant analgesic activity (p0.05 in comparison with morphine).Conclusion: Different extracts of M. astracanicum demonstrated antinociceptive activity that support the traditional usage of Marrubium genus for the treatment of arthritis, gout and other inflammatory diseases.